UJI LAPANGAN ALAT PRODUKSI GARAM BERYODIUM BERSKALA KECIL DI DAERAH GANGGUAN AKIBAT KURANG YODIUM - Hermana Hermana; Mien Karmini; Suryana Purawisastra (Persagi, 1998)
The problem in supplying iodine to people suffering from iodine deficiency disorders are technique to produce iodated salt and the great distance between producers and consumers. The delivery of iodine would be more effective if production of iodated salt is carried out near or in areas of iodine deficiency disorders. Nutrition Research and Development Centre, Ministry of Health, RI has produced a small-scale salt iodation plant. The plant has been tested in the laboratory. Field trial of the plant was carried out in collaboration with the Village Cooperatives Unit (Koperasi Unit Desa) at Bulu Cindeo, District of Pangkajene and Kepulauan, South Sulawesi. Locally-produced salt was iodated. The product was distributed not only in Pangkep but in neighbouring districts as well. It was observed that the small scale iodation plant was an appropriate technology for village level. It could be operated by man powers having minimum education (primary school). The production unit needs a not-too-big investment to run the plant During the trial, the Cooperatives learned that the plant was efficient and was economically profitable. The availability of iodated salt in the area, resulted in increased consumption.Keywords: salt iodation, iodation machine.